Cytogenetics characterization of Minthostachys mollis (Kunth.) Griseb. Populations from Tucumán province (Argentina) - Pastoriza, Adriana del Valle; Budeguer, Carlos Jorge; Elechosa, Miguel Angel; Juarez, Miguel Angel; Molina, Ana Maria (Facultad de Agronomía y Zootecnia, Universidad Nacional de Tucumán, 2019)
Minthostachys mollis (Kunth.) Griseb. (Lamiaceae) is a native species from the central and northwest Argentinean region. Reported a chromosome number are 2n = 24 and 2n = 42. In this work, two populations of M. mollis were cytogenetically characterized in Tucumán province, Argentina, by means of mitosis and meiosis analysis, with material from Río Nío and Villa Padre Monti (Burruyacú, Tucumán). For the mitosis and meiosis analysis, the preparations were made with 2 % haematoxylin as colorant. The pollen grain viability was assessed by using cotton blue in lactophenol technique. Results showed a chromosome number 2n = 48 for both studied populations. In meiosis analysis, normal as well as abnormal divisions in different percentage were observed. Among the abnormalities, multivalent, dyads, triads and polyads of different degree and size were observed. Also, configurations like abnormal spindle orientation, laggard chromosomes and micronucleus in variable percentage were observed. The pollen viability analysis showed 87.2 % of viable pollen grains. The new chromosomal number found in M. mollis could be owing to: a) Formation of gametes (n = 24) from population of Villa Padre Monti and Rio Nio. b) In sympatric zones, with species 2n = 24 and 2n =42, could take place the union of non-reduced gametes (4x = 24), and gametes 4x from those of heptaployds 2n = 42, resulting the populations with 2n = 48. These results constitute a basis in order to perform further studies about the reproductive biology of this species.